Konten Review Film, Kualitas Informasi dan Minat Menonton Film - Sutandi, Felicitas Velin; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The current growth of the film industry continues to increase, which means that film production houses must be able to attract the attention of consumers so that it is commensurate with the costs incurred and the hard work done. Review content on social media, especially TikTok, is one of the determining factors in the high interest in watching the community. Against this background, this study aims to determine the effect of exposure to film review content and the quality of information on the TikTok @kepinhelmy account on interest in watching films. This research is quantitative using a survey method. Samples were taken from 100 respondents using the Slovin formula, and based on nonprobability sampling techniques. Primary data was collected with a Likert scale questionnaire 1-5. Data processing used is multiple linear regression technique and hypothesis testing using SPSS 25 for windows. From the test obtained valid and reliable results. Multiple regression tests and hypothesis testing show that the results of Ha1 and Ha2 are acceptable, so it can be concluded that there is an influence between exposure to film review content and the quality of information on the TikTok @kepinhelmy account on interest in watching a film. Pertumbuhan industri film saat ini terus meningkat yang membuat rumah produksi film harus bisa menarik perhatian konsumen agar sebanding dengan biaya yang dikeluarkan dan kerja keras yang dilakukan. Konten review pada media sosial terkhususnya TikTok menjadi salah faktor penentu dalam tingginya minat menonton masyarakat. Dengan latar belakang hal tersebut penelitian ini bertujuan untuk mengetahui pengaruh terpaan konten review film dan kualitas informasi di akun TikTok @kepinhelmy terhadap minat menonton film. Penelitian ini bersifat kuantitatif menggunakan metode survei. Sampel diambil dari 100 responden dengan menggunakan rumus Slovin, dan berdasarkan teknik nonprobability sampling. Data primer dikumpulkan dengan kuesioner skala likert. Pengolahan data yang digunakan adalah teknik regresi linier berganda serta pengujian hipotesis memakai SPSS 25 for windows. Dari pengujian didapatkan hasil valid dan reliabel. Uji regresi berganda dan pengujian hipotesis memperlihatkan hasil Ha1 dan Ha2 dapat diterima, sehingga dapat disimpulkan terdapat pengaruh antara terpaan konten review film dan kualitas informasi di akun TikTok @kepinhelmy terhadap minat menonton sebuah film.